2022
DOI: 10.1038/s41598-022-22823-8
|View full text |Cite
|
Sign up to set email alerts
|

Vasectomy reversal outcomes in men after testosterone therapy

Abstract: The prevalence of males on testosterone therapy (TT) seeking vasectomy reversal (VR) is rising. As medical therapy (MT) to recover spermatogenesis after TT has been previously described, our study’s objective is to present our institution’s management and outcomes of VR in men previously on TT. We performed a retrospective case series of vasectomy patients on TT with subsequent VR by a single microsurgeon between March, 2010 and March, 2022. 14 men undergoing VR during the study period met inclusion criteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The current investigation represents that largest analysis of the impact of TT on VR outcomes published to date. Consistent with the findings of the current study, a retrospective case series of 14 men by Bash et al ( 2022) 8 reported high rates of VV (96%) and sustained patency rates among patients using TT prior to VR. Moreover, Coward et al (2014) 9 reported an overall patency rate of 83% with spontaneous pregnancy rates of 50% among 6 men with prior TT, suggesting that VR after TT can have outcomes comparable to those in the general population.…”
Section: Discussionsupporting
confidence: 91%
“…The current investigation represents that largest analysis of the impact of TT on VR outcomes published to date. Consistent with the findings of the current study, a retrospective case series of 14 men by Bash et al ( 2022) 8 reported high rates of VV (96%) and sustained patency rates among patients using TT prior to VR. Moreover, Coward et al (2014) 9 reported an overall patency rate of 83% with spontaneous pregnancy rates of 50% among 6 men with prior TT, suggesting that VR after TT can have outcomes comparable to those in the general population.…”
Section: Discussionsupporting
confidence: 91%
“…Ultimately, 95 studies were included in this review. Eighty studies were included in the quantitative analyses, 25–104 whereas 15 studies were only included in the quantitative synthesis (Figure 1). 105–119 …”
Section: Resultsmentioning
confidence: 99%